Characteristics Study and Development of Solid Fuel Briquette From Sarawak Coal - Yusup, Nasrullah (2018)
The author had been given a task in making study and analysis on development of solid fuel briquette from Sarawak coal. Throughout this project, the author would like to investigate the problem statement of this issue which were the best mixing ratio of coal and palm fibre in development of fuel briquette. Besides that, the differences of Sarawak coal properties will affect the performance of the briquette.